NRSN2 is a Prognostic Biomarker in Gastric Cancer and Facilitates the Growth and Migration of Gastric Cancer Cells - Ren, Shenghui; Chen, Manyu; Chen, Yu; Ding, Ke (Protein and Peptide Letters, 2023)
Background: Neurensin-2 (NRSN2) is reported to be associated with the progression of many tumors. This work aimed at investigating the biological function and prognostic significance of NRSN2 in gastric cancer (GC). Methods: NRSN2 expression in various cancer tissue was analyzed by the TIMER database. NRSN2 expression in GC tissue samples of different groups was analyzed by the UALCAN database. The survival analysis was performed with the Kaplan-Meier database. NRSN2 expression in GC tissues and cell lines was measured by qRT-PCR and Western blot. CCK-8, Transwell and scratch healing assays were conducted to detect the proliferative, migrative and invasive capabilities of GC cells, respectively. The LinkedOmics database and StarBase database were utilized to analyze the related genes with NRSN2 in GC. The association of NRSN2 expression with tumor immune infiltrating cells and molecular markers of immune cells was investigated with the TIMER database. Results: NRSN2 expression was up-regulated in GC tissues, which was correlated with GC tumor grade, lymph node metastasis, and TP53 mutation. The prognosis of GC patients with high NRSN2 expression was worse than those of the patients with low NRSN2 expression. NRSN2 expression was also associated with the TNM stage, and Lauren subtype of GC patients. NRSN2 overexpression promoted the growth, migration and invasion of GC cells lines; knocking down NRSN2 worked oppositely. NRSN2 expression in GC was associated with Wnt, p53, and NOD-like receptor signaling pathways. NRSN2 expression was also significantly associated with the infiltration of CD8+ T cells, CD4+ T cells, macrophages, neutrophils, and dendritic cells in the GC microenvironment. Conclusion: NRSN2 expression in GC tissues is up-regulated, which correlates with a poor prognosis and immune cell infiltration of GC patients. NRSN2 facilitates the growth and aggressiveness of GC cells, implying that it may be a diagnostic biomarker and therapy target for GC.
Keywords: immune infiltration